ChemInform Abstract: Lanthanum Lead Oxide Hydroxide Nitrates with a Nonlinear Optical Effect. Issue 6 (February 2015) - Wang, Genxiang; Luo, Min; Lin, Chensheng; Ye, Ning; Zhou, Yuqiao; Cheng, Wendan
Abstract Crystals of [LaPb8O(OH)10(H2O)] (NO3)7 (I) and [LaPb8O(OH)10(H2O)] (NO3)7·2H2O (II) are hydrothermally synthesized under subcritical conditions from mixtures of Pb(NO3)2, H2O, and 0.5 and 1 equiv.